The Influence of Physical Work Environment on Employee Performance of PT United Tractors Tbk Makassar Branch - Musdalifah Musdalifah; Sirajuddin Saleh; Risma Niswaty (ASHA Publishing, 2024)
Without a good physical work environment, employees will not be able to carry out their duties properly according to the demands of the company. Not only does it have an impact on employee performance directly but it can also contribute to the overall success of the company. Investing in improving the physical work environment can yield significant results in terms of productivity, employee satisfaction, and company success. The type of research used is quantitative descriptive research. The indicators of the physical work environment include lighting, air temperature, noise, use of color and movement space. The employee performance indicators include quality, quantity, and punctuality. The sample in this study was 50 people. The data collection techniques used are observation, questionnaire and documentation. The data obtained was processed using the SPSS 26 application which consisted of validity tests, reliability tests, data analysis techniques used were descriptive statistical tests, data normality tests, product moment correlation analysis, and simple linear regression analysis. Based on the results of a simple linear regression analysis, it can be concluded that the physical work environment variable has a positive and significant effect on the performance variable of employees of PT United Tractors Tbk Makassar Branch even though the contribution has not reached a very high level. This is reviewed from the significant value between the two variables, namely variable X (physical work environment) and variable Y (employee performance).